Cost of Living Pressure and Work Anxiety: A Qualitative Study on Employees of PT. LSP Fasilitator Instruktur and Coaching Staff - Eva Rosmalia; Imam Bustomi; Hartawati Rosmery; Rilla Sovitriana (Siber Nusantara of Education and Sport Review, 2026)
The rising cost of living in recent years has become a phenomenon that affects not only economic conditions but also the psychological well-being of workers. The imbalance between income and increasing life needs gives rise to financial strain—defined as an individual's perception of insufficient financial resources (Butterworth et al., 2020)—which has the potential to trigger work anxiety. This study aims to understand the subjective experiences of employees in facing cost of living pressures and their implications for work anxiety. This study employed a qualitative approach using a phenomenological method. Data was collected through in-depth interviews with five employees selected by purposive sampling. Data analysis was conducted using thematic analysis. The findings indicate that cost of living pressure is perceived as financial insecurity that triggers work anxiety and alters the perception of employment as the primary source of economic stability. Furthermore, economic pressure does not solely produce distress; it may also function as eustress that enhances work motivation. The novelty of this study lies in the integration of financial strain, job insecurity, and coping strategies to explain the dynamics of employees' psychological adaptation.